Desaturase-dependent secretory functions of hepatocyte-like cells control systemic lipid metabolism during starvation in Drosophila - Li, Jiayi; Huang, Kerui; Dibra, Indira; Liu, Ying; Perrimon, Norbert; Simons, Matias (Nature Communications, 2025)
Similar to the mammalian hepatocytes, Drosophila oenocytes accumulate fat during fasting, but it is unclear how they communicate with the fat body, the major lipid source. Using a modified protocol for prolonged starvation, we show that knockdown of the sole delta 9 desaturase, Desat1 (SCD in mammals), specifically in oenocytes leads to more saturated lipids in the hemolymph and reduced triacylglycerol storage in the fat body as well as reduced survival. We further show that the insulin antagonist ImpL2 (IGFBP7 in mammals) is secreted from oenocytes during starvation in a Desat1-dependent manner. Flies with oenocyte-specific knockdown and overexpression of ImpL2 exhibit higher and lower sensitivity to starvation, lower and higher triacylglycerol levels as well as higher and lower levels of bmm during starvation, respectively. Overall, this study highlights the importance of Desat1 in maintaining the proper functioning of oenocytes and the central role of oenocytes in the regulation of fat body lipid metabolism during periods of prolonged starvation.
Gesehen am 02.03.2026